LEARNING MODELS FOR LIFELONG LEARNING IN DIGITAL AGE - Boonying, Varinthorn (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The research objectives were to study the needs of learning models for lifelong learning in digital age and to propose learning models for lifelong learning in digital age in Thailand. The research methodology was qualitative, based on documentary analysis, online panel discussion, and suggestions by 200 experts were as follows: (1) academics and teachers (2) councils, associations, foundations and private organizations related to education and the media/online media (3) organizations representing audiences, listeners, media consumers, children/youth, civil society organizations covering the Northern region, Northeast, East, South and Bangkok/perimeter (4) specialized experts in the development and behavior of children, youth and families. The findings revealed as follows: (1) the needs learning models for lifelong learning found limitations of instructional media for the development of knowledge/subjects/topics that were important to promoting child development and Thai youth suitable for each age range (2) knowledge and content of online media that can help develop learning in various areas for all ages (3) characteristics of online platforms to strengthen a learning society on online media that can attract and arouse the interest of the target group to make them interested in learning in the system. The Learning Models of appropriate media contents to promote a learning society for children and youth through online media for children and youth should be integrated physical, social emotional, intellectual (learning characteristics integrated (STEAM Education) with the base of social studies and English language development and enhancing life skills (soft skills), professional skills for career and digital skills.